Measuring optical properties of human liver between 400 and 1000 nm - Carneiro, Isa (2019)
Laser diagnostics and treatment procedures are commonly performed for visible and near-IR wavelengths. The knowledge of the wavelength dependences for the optical properties of various biological tissues in this spectral range is useful for clinical applications. Since the optical properties of human liver have been previously known only for near-IR wavelengths, the aim is to estimate their wavelength dependences between 400 and 1000 nm. Using spectral measurements from liver samples in this range, we determine their optical properties with the inverse adding-doubling method. The obtained results indicate the presence of bile, oxyhaemoglobin and deoxyhaemoglobin in human liver. The combination of these biological components results in strong absorption for wavelengths between 400 and 600 nm, with peaks at unusual wavelengths. For wavelengths above 600 nm, the wavelength dependences for all optical properties present the typical behavior, but strong and shifted absorption observed for wavelengths below 600 nm has been previously unknown and can be useful for clinical procedures with lasers working in this range.